Failure of fear extinction in insomnia: An evolutionary perspective. (June 2020) - Perogamvros, Lampros; Castelnovo, Anna; Samson, David; Dang-Vu, Thien Thanh
Summary: The pathophysiology of insomnia remains poorly understood, yet emerging cross-disciplinary approaches integrating natural history, observational studies in traditional populations, gene-phenotype expression and experiments are opening up new avenues to investigate the evolutionary origins of sleep disorders, with the potential to inform innovations in treatment. Previous authors have supported that acute insomnia is a normal biopsychosocial response to a perceived or real threat and may thus represent an adaptive response to stress. We further extend this hypothesis by claiming that insomnia reflects a fear-related evolutionary survival mechanism, which becomes persistent in some vulnerable individuals due to failure of the fear extinction function. Possible treatments targeting fear extinction are proposed, such as pharmacotherapy and emotion-based cognitive behavioral therapy.